2020
DOI: 10.3390/en13112797
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Mitigation in Households between Market Failures and Psychological Barriers

Abstract: Though there are areas of climate change mitigation linked to household’s energy consumption having huge greenhouse gas (GHG) emission reduction potential as energy renovation or installation of micro generation technologies using renewable energy sources, these GHG emission reduction potentials are not realized so far. The main input of the paper is to overcome this gap and to provide a systematic review of the main barriers of climate change mitigation behavior linked to energy consumption in households and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Similarly, some factors positively affect i4.0 adoption, such as human resources, production systems-based resources, project management resources, management leadership-based resources, green logistics & design resources, information technology, big data analytics, and collaborative relationships [ 18 ]. However, psychological and behavioral barriers have not been appropriately addressed in the literature [ 19 ]. Several studies are limited to the technological side, insufficiently considering social aspects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some factors positively affect i4.0 adoption, such as human resources, production systems-based resources, project management resources, management leadership-based resources, green logistics & design resources, information technology, big data analytics, and collaborative relationships [ 18 ]. However, psychological and behavioral barriers have not been appropriately addressed in the literature [ 19 ]. Several studies are limited to the technological side, insufficiently considering social aspects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to motivations, the rates for different EERs are determined by different contextual factors that influence, such as building and household characteristics, and personal factors, such as attitudes and perceptions about energy consumption. More importantly, recent research has identified cognitive biases of the category of personal factors as an important barrier to EERs (De Vries et al, 2019;Klöckner & Nayum, 2017;Streimikiene et al, 2020;Wilson et al, 2018). However, empirical research into the exact nature of the cognitive biases and the effectiveness of interventions to de-bias are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote home renovations, private homeowners need to be informed and persuaded to use such instruments [13]-for example, Energy Performance Certificates (EPC) [14], financial incentives [15,16], neighbourhood renovation schemes [17], group buying schemes [17], and so on-and authorities need to arrange supporting marketing and campaigns. In European countries, some key barriers to home energy renovations are insufficient awareness of the building users [18,19], biased consultations [20], the decision-making process [21], or difficulty accessing finance and certified experts [16].…”
Section: Introductionmentioning
confidence: 99%
“…This makes it highly relevant to analyse pop-up centres through the lens of business models. The business model focuses on creating, delivering, and capturing values, consisting of customer segments, value propositions, communication channels, customer relationships, key activities, key resources, key partners, revenue streams, and the cost structure [19].…”
Section: Introductionmentioning
confidence: 99%